THE INFLUENCE OF DHARMAGITA’S ON COGNITIVE FUNCTION IN ELDERLY - Ni Putu Emy Darma Yanti (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2016)
Cognitive impairment is a condition that negatively impacts the survival of the elderly. Dharmagita is a spiritual song that is one of the sensory stimulation techniques that are good for the elderly. Singing a song may stimulate the release of endorphins and serotonin that can trigger somebody’s thinking and learning. Dharmagita Award is intended to provide sensory stimuli in the elderly so that they can improve the cognitive function of the elderly. This study aimed to determine the effect of Dharmagita on the cognitive function of the elderly. This study was a pre-experimental study with a one-group pretest-posttest design. The sample consisted of 12 elderly people selected by purposive sampling. The data collection was done by using the MMSE questionnaire. The results showed the average scores of the cognitive function before and after Dharmagita, which were 23.92 and 25 respectively. Based on the statistical results using a paired t-test, there were significant differences in cognitive function with the significance level p = 0.001 meaning that there was Dharmagita influence on the cognitive function of the elderly. Therefore, it is recommended to the elderly, caregivers and policy makers to use Dharmagita in improving the cognitive function of the elderly.Keywords: Cognitive function, Dharmagita, Mini Mental Status Examination